2017
DOI: 10.1016/j.expthermflusci.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tagging velocimetry by direct phosphorescence in gas microflows: Correction of Taylor dispersion

Abstract: Molecular tagging velocimetry is a little-intrusive technique based on the properties of specific molecules able to emit luminescence once properly excited. Several variants of this technique have been successfully developed for analyzing external gas flows or internal gas flows in large systems. There is, however, very few experimental data on molecular tagging velocimetry for gas flows in mini or microsystems, and these data are strongly affected by the molecular diffusion of the tracer molecules. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…However, the image data revealed that these effects are negligible, and the Gaussian function is still representative of the light distribution in the gas flow direction. As it has been done in previous works [12,14,20], the Gaussian fitting applied to each horizontal line of pixels at any position y = y j is…”
Section: Mtv Image Post-processingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the image data revealed that these effects are negligible, and the Gaussian function is still representative of the light distribution in the gas flow direction. As it has been done in previous works [12,14,20], the Gaussian fitting applied to each horizontal line of pixels at any position y = y j is…”
Section: Mtv Image Post-processingmentioning
confidence: 99%
“…In this section, the MTV technique was applied to acetone-seeded argon flows in non-rarefied conditions. The previous works of Samouda et al [12] and Si-Hadj Mohand et al [14] already demonstrated the successful application of MTV for velocity measurements in channel gas flow in non-rarefied conditions by using as a tracer acetone vapor excited at 266 nm. Si Hadj Mohand et al were not able to apply MTV for pressures lower than about 42 kPa because of the low signal intensity due to the limited phosphorescence quantum yield of acetone excited at 266 nm.…”
Section: Mtv Measurements Of Channel Gas Flows In Non-rarefied Conditmentioning
confidence: 99%
See 1 more Smart Citation
“…1D-MTV by direct phosphorescence has already been applied to non-rarefied external supersonic or hypersonic turbulent gas flows [23,24], to rarefied supersonic jets [25] and to non-rarefied gas flows in millimetric channels [26,27]. However, some difficulties have prevented until now the successful application of this technique to confined rarefied gas flows.…”
Section: Introductionmentioning
confidence: 99%
“…A reconstruction method of the velocity profile from the displacement profile was developed and validated with numerical experiments. Si Hadj Mohand et al [27] successfully applied this reconstruction method on MTV data in a millimetric channel and correctly extracted the velocity profile at atmospheric and sub-atmospheric pressures down to a minimum average pressure of 50 kPa. At this pressure level in a 1-mm deep channel, the flow is still in a nonrarefied regime.…”
Section: Introductionmentioning
confidence: 99%